Mineralized Granitic Porphyry of the Yangla Copper Deposit, Western Yunnan, China: Geochemistry of Fluid Inclusions and H-O, S, and Pb Isotopes - Xinfu Wang; Bo Li; ShenJin Guan; Olivier Nadeau; Guo Tang (Geofluids)
The Yangla copper deposit (YCD) is located in the central part of the Jinshajiang tectonic belt (Jinshajiang metallogenic belt) and is one of the most important copper deposits which has the large-scale copper reserves of the northwestern Yunnan, China. The ore bodies are strictly controlled by the stratum, pluton, and structure, which are layered, lens, and vein-like within the contact or fracture zone of the pluton and surrounding rock. At Yangla, two styles of mineralization occur at the brecciated contact zone between the pluton (granodiorite and granitic porphyry) and carbonaceous wall rock and include strata bound/lens-shaped replacement of carbonate rocks (skarn style) and porphyry-style sulfide-quart-calcite veins. But, the granitic porphyry mineralization have received less attention; the isotope and fluid inclusion studies are relatively scarce for limited porphyry ore bodies that have been discovered at the YCD. Quartz-hosted fluid inclusions from the recently discovered granitic porphyry have homogenization temperature averaging around 180±20°C and 300±20°C with salinities ranging from 4 to 22 wt.% NaCleq, pointing toward the contribution of medium temperature-medium salinity and low temperature-low salinity fluids during the metallogenesis. These fluid inclusions have δ18OH2O values ranging between -1.91‰ and -1.02‰ and δD values ranging between -143.10‰ and -110‰, suggesting that the ore-forming fluid was a mix of magmatic and meteoric water. Ore-related pyrite/chalcopyrite have δ34SV-CDT values ranging from -1.0‰ to 1.0‰ and whole rocks have δ34SΣS = 0.34, suggesting that sulfur mainly derived from magmatic rocks of the Yangla mining area. The sulfides 208Pb/204Pb ranged from 38.8208-38.9969, 207Pb/204Pb from 15.7079-15.7357, and 206Pb/204Pb from 18.5363-18.7045, indicating that the lead mainly originated from the upper crust. It is demonstrated that the evolution of ore-forming fluid is continuous from the skarn ore body (SOB) stage to the porphyritic ore body stage and belong to the products of the same ore-forming fluid system, and the unisothermal mixing and cooling actions were maybe the main mechanism at the metallic minerals precipitation in mineralized granitic porphyry (MGP). A model is proposed according to the early stage, a magmatic fluid reacted and replaced with the surrounding carbonate rocks and then formed skarn-type ore bodies. The magmatic-hydrothermal fluid subsequently deposited porphyry-type quartz-calcite veins, veinlets, and stockwork mineralization.